Y2K - Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 1998)
As the millennium draws to an end, the threat posed by the Year 2000 (Y2K) problem is inducing vast private and public spending on its remediation. In this paper, we model the Y2K problem as an anticipated, permanent loss in output whose magnitude can be lessened by investing resources in advance. We embed the Y2K problem into a dynamic general equilibrium framework and show that our model replicates three observed characteristics of the dynamics triggered by the Y2K bug: (1) Precautionary investment: investment in solving the Y2K problem begins before the year 2000; (2) Investment delay: although economic agents have been aware of the Y2K problem since the 1960s, investment did not begin until recently; (3) Investment acceleration: as the new millennium approaches, the amount of resources allocated to solving the Y2K problem increases. Furthermore, the model predicts that output net of resources devoted to solving the Y2K problem need not decline in 2000.
Keywords: E22; E32; 330; investment dynamics; Y2K problem